2015
DOI: 10.1158/1535-7163.mct-15-0062
|View full text |Cite
|
Sign up to set email alerts
|

MEK Inhibition Overcomes Cisplatin Resistance Conferred by SOS/MAPK Pathway Activation in Squamous Cell Carcinoma

Abstract: Genomic analyses of squamous cell carcinoma (SCC) have yet to yield significant strategies against pathway activation to improve treatment. Platinum-based chemotherapy remains the mainstay of treatment for SCC of different histotypes either as a single-agent or alongside other chemotherapeutic drugs or radiotherapy; however, resistance inevitably emerges, which limits the duration of treatment response. To elucidate mechanisms that mediate resistance to cisplatin, we compared drug-induced perturbations to gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 48 publications
2
40
0
1
Order By: Relevance
“…The primary anticancer mechanism of platinum is to bind covalently to DNA and form platinum-DNA adducts, which results in apoptosis, 30 and apoptosis dysregulation is one of the primary mechanisms underlying cisplatin resistance. 22, 31, 32 In this paper, we reported that BST2 inhibited cisplatin-induced apoptosis in NPC cells and that this effect may be associated with upregulation of anti-apoptotic factors. Specifically, knockdown of BST2 downregulated the anti-apoptotic factors (such as Bcl-X L and livin), whereas overexpression of BST2 upregulated these factors in NPC cells.…”
Section: Discussionmentioning
confidence: 86%
“…The primary anticancer mechanism of platinum is to bind covalently to DNA and form platinum-DNA adducts, which results in apoptosis, 30 and apoptosis dysregulation is one of the primary mechanisms underlying cisplatin resistance. 22, 31, 32 In this paper, we reported that BST2 inhibited cisplatin-induced apoptosis in NPC cells and that this effect may be associated with upregulation of anti-apoptotic factors. Specifically, knockdown of BST2 downregulated the anti-apoptotic factors (such as Bcl-X L and livin), whereas overexpression of BST2 upregulated these factors in NPC cells.…”
Section: Discussionmentioning
confidence: 86%
“…A). Interestingly, lung SCC cells (H2066, SW900, H2170, Calu‐1, H520, and SK‐MES‐1), which we previously demonstrated to exhibit decreased sensitivity to cisplatin, were highly sensitive to belinostat (Kong et al ., ). The reciprocally inverse sensitivity among belinostat and cisplatin suggested the potential for synergistic combination.…”
Section: Resultsmentioning
confidence: 97%
“…The present study shows that a belinostat/cisplatin combination is broadly effective across a panel of lung SCC cell lines, with a strong inhibition of MAPK and SOS. Our group has previously described the significance of SOS/MAPK activation in cisplatin resistance (Kong et al ., ). On the basis of this study, we speculate that belinostat treatment promotes ubiquitin‐proteasome activity in SCC cells; however, cisplatin‐resistant cells that exploit SOS/MAPK activation for survival are more susceptible to belinostat treatment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations